Correlation functions for non-conformal Dp-brane holography - Nikolay Bobev; Guillermo Mera Álvarez; Hynek Paul (Journal of High Energy Physics)
Abstract We use holography to study correlation functions of local operators in maximally supersymmetric Yang-Mills theories arising on the world-volume of Dp-branes in the large-N and strong-coupling limit. The relevant supergravity backgrounds obtained from the near-horizon limit of the Dp-branes enjoy a scaling similarity, which leads to an auxiliary AdS space of fractional dimension. This suggests that holographic correlation functions in this setup can be computed by integrating standard CFT correlators over the auxiliary extra dimensions. We apply this prescription to analytically compute two- and three-point correlators of scalar operators. The resulting two-point functions take a familiar CFT form but with shifted conformal dimensions, while the three-point correlators have a much more involved position dependence which we calculate explicitly in terms of a sum of Appell functions.